Kajian Perbandingan Atas Perlindungan Hukum terhadap Pekerja Anak di Indonesia dan Negara Lain - Yulius Efendi (Pusat Riset dan Inovasi Nasional, 2023)
In principle, every sovereign country that is at an advanced and developing stage has a concrete legal and constitutional basis to regulate the wheels of government in each independent and sovereign country. There is no exception in the regulation and existence of the workforce as one of the foreign exchange contributors to state finances. However, the issue of child labor in Indonesia is still a problem that has not been fully resolved by stakeholders, in this case the Indonesian government. On the other hand, other countries also experience the same problem, so in this research a comparison of regulations relating to child labor is carried out. In the above problem, it is hoped that the government will immediately find a solution to this matter so that children can be returned to their position to receive education and other rights as regulated in the 1945 Constitution of the Republic of Indonesia.